Political Rents in a Non-Corrupt Democracy - Helena Svaleryd; Jonas Vlachos (Research Institute of Industrial Economics (IFN), 2007)
A fundamental problem in all political systems is that the people in power may extract rents to the detriment of the general public. In a democracy, electoral competition and information provided by the media may keep such rent extraction at bay. We develop a simple model where rents are decreasing in the degree of political competition and voter information. In line with our theoretical predictions, we find that both increased political competition and increased local media coverage substantially reduce direct measures of legal political rents among local governments in a non-corrupt democracy (Sweden).
Keywords: D72; H10; H70; 330; Accountability; Political Competition; Media; Political Rents; Politisches System; Demokratie; Macht; Rent-Seeking; Medienrecht; Schweden